2019
DOI: 10.1111/jsbm.12468
|View full text |Cite
|
Sign up to set email alerts
|

Customer Orientation and Performance of Women‐Owned Businesses: A Configurational Approach

Abstract: The present research aims to improve the current understanding of the relationship between customer orientation and performance of women-owned businesses. This study proposed that risk-taking and financial capital are vital moderating factors of this relationship. Additionally, the study postulates that new insights can be unearthed by combining these factors with customer orientation in a three-way interaction model. Using a sample of 264 women entrepreneurs, the results showed that (a) customer orientation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 94 publications
(234 reference statements)
3
41
0
1
Order By: Relevance
“…Others have posited that in today's competitive business environments, businesses that have knowledge about, and understand, their customers gain competitive advantage (Kumar et al, 2006;Pérez-Luño et al, 2016) through providing products that customers need, which leads to improved customer relationship management, customer satisfaction, and loyalty (Anderson et al, 2007). According to Neneh (2019), successful businesses, specifically in the MB retail sector, are those that have sufficient knowledge of the customers' needs and the prevailing products that the customers are willing to buy to meet their needs. Polo Peña et al 2016argue that successful businesses are those that design and implement customer-oriented business strategies.…”
Section: Knowledge About Customers and Productsmentioning
confidence: 99%
“…Others have posited that in today's competitive business environments, businesses that have knowledge about, and understand, their customers gain competitive advantage (Kumar et al, 2006;Pérez-Luño et al, 2016) through providing products that customers need, which leads to improved customer relationship management, customer satisfaction, and loyalty (Anderson et al, 2007). According to Neneh (2019), successful businesses, specifically in the MB retail sector, are those that have sufficient knowledge of the customers' needs and the prevailing products that the customers are willing to buy to meet their needs. Polo Peña et al 2016argue that successful businesses are those that design and implement customer-oriented business strategies.…”
Section: Knowledge About Customers and Productsmentioning
confidence: 99%
“…Competitiveness is linked to a number of adaptive characteristics and aspects of success including need to achieve (Smither & Houston, 1992) as well as self-efficacy, conscientiousness, and performance (Brown, Cron, & Slocum, 1998). Recently, Neneh (2018) found that competitiveness mediates the process of opportunity recognition and action taking that is associated with success and achievement. While several lines of inquiry support the conceptual link between grit and competitiveness, research by Dugan, Hochstein, Rouziou, and Britton (2019) provides empirical evidence linking competitiveness and grit, finding they are positively correlated and both predict higher sales performance.…”
Section: Study 1: the Bright And Dark Aspects Of Gritmentioning
confidence: 99%
“…In addition, the fact that customer-oriented enterprises can better and effectively adjust their products and services to meet market demand gives them a competitive advantage and can easily surpass their competitors (Feng et al, 2012;Ziggers and Henseler, 2016). This view is supported by many studies (Neneh, 2019;Pongwirithon and Awirothananon, 2014), which report a significant positive correlation between customer orientation and performance.…”
Section: The Effect Of Customer Orientation On Mne Performancementioning
confidence: 91%
“…Customer-oriented enterprises usually obtain information from customers and use it to formulate appropriate strategies to meet the general needs of customers. It is for this reason that customer orientation is an essential element of performance (Neneh, 2019). Through literature review, scholars generally agree that the service process is closely related to customer value, on the other hand, they also agree that customer orientation promotes enterprise performance.…”
Section: The Effect Of Customer Orientation On Mne Performancementioning
confidence: 99%